DETERMINISTIC MULTI-OBJECTIVE LIGHTWEIGHT DESIGN OF C-BEAM BASED ON RESPONSE SURFACE AND GENETIC ALGORITHM - CHEN HaoRan; XIANG ZhongKe; CHENG WenMing; XIANG FeiFei (Jixie qiangdu)
The lightweight design of C-beam structure which is a key structure component of bus air suspension will be mainly discussed in this paper. Firstly,based on parameterized calculating system,the finite element model that is in line with the actual working condition was established. Meanwhile,the maximum equivalent stress,bending stiffness and fatigue life analysis were completed. Then the central composite design experimental method was used,and the response surface model（ RSM） was fitted based on full 2 nd order polynomials,and design variables were screened according to sensitivity analysis.Finally,take the minimum mass as well as maximum bending stiffness as the objective function. At the same time,the maximum equivalent stress and the fatigue life of 500,000 cycles are taken as the constraint conditions. The optimization was conducted by NSGA-II multi-objective genetic algorithm,and in series Pareto non-inferior front curve was obtained,and the compromising solution was selected according to the actual design needs. The results indicate that the bending stiffness of the lightweight cbeam basically stay the same as before without changing the original material and meeting the constraint conditions,and the weight loss is 2. 68 kg and the weight loss ratio is 3. 6%.